Degradation and recovery of the emission from a graphite cathode in relation to the repetition frequency of nanosecond accelerating pulses; IEEE Transactions on Plasma Science; Vol. 34, № 5 pt. 1 - Korovin S. D.; Litvinov E. A.; Rukin S. N.; Shpak V. G.; Yalandin M. I.; Mesyats G. A. Gennady Andreyevich; Rostov V. V. (2006, 2006)
В фонде НТБ ТПУ отсутствует